Research on Intelligent Logistics UAV - Hai-Wu Lee (IAES International Journal of Robotics and Automation (IJRA), 2022)
As unmanned aerial vehicle (UAV) starts to be frequently used in the fields of industry, agriculture, reconnaissance and logistics, flight research involving UAV also starts to cover a wider range. In the civil field, UAV is generally used as an auxiliary tool to deal with urban problems, but buildings are the main factors hindering the flight of UAV. Therefore, it is necessary to find out the optimal flight path of   UAV under certain constraints. The intelligent logistics UAV proposed in this paper is used to replace the courier to deliver small goods and process the fuzzy images taken along the way. It is a quad copter implementation plan integrating flight control, obstacle avoidance ultrasound, mobile APP control system and webcam. Gradient descent algorithm and improve Proportion-Integral-Differential (PID) controller are applied in UAV flight control system, MATLAB and wavelet transform to handle fuzzy image. In addition, using ant colony algorithm and adaptive strategy to realize the path planning of UAV. The UAV can detect surrounding obstacles during flight, and the ground control station receives feedback information and makes emergency treatment to ensure safe flight.